2018
DOI: 10.30773/pi.2016.12.31
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Number of Manic Episodes and Oxidative Stress Indicators in Bipolar Disorder

Abstract: ObjectiveBipolar disorder (BD) is a chronic mood disorder characterized by recurrent episodes that has a lifetime prevalence of 0.4–5.5%. The neurochemical mechanism of BD is not fully understood. Oxidative stress in neurons causes lipid peroxidation in proteins associated with neuronal membranes and intracellular enzymes and it may lead to dysfunction in neurotransmitter reuptake and enzyme activities. These pathological processes are thought to occur in brain regions associated with affective functions and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Finally, the combined analysis of SOD + CAT activity, which is a measure of antioxidant status, showed a significant increase in patients with BD vs HCs. A previous study found an elevated total antioxidant capacity in patients with BD vs HCs, irrespective of the number of manic episodes 52 . In our analysis, increased SOD + CAT activity was also observed in patients with a symptomatic affective phase of the disease, but not in those with euthymia, with differences according to manic or depressive polarity.…”
Section: Discussionsupporting
confidence: 71%
“…Finally, the combined analysis of SOD + CAT activity, which is a measure of antioxidant status, showed a significant increase in patients with BD vs HCs. A previous study found an elevated total antioxidant capacity in patients with BD vs HCs, irrespective of the number of manic episodes 52 . In our analysis, increased SOD + CAT activity was also observed in patients with a symptomatic affective phase of the disease, but not in those with euthymia, with differences according to manic or depressive polarity.…”
Section: Discussionsupporting
confidence: 71%
“…Menegas et al (2020), using the methamphetamine administration model of mania, also observed correlations between hyperlocomotion and lipid damage parameters in the striatum of rats. Clinically, a positive correlation between mania severity (Young Mania Rating Scale) and peripheral oxidative stress index was also (Akarsu et al, 2018) observed which supports the relevance of our pre-clinical approach.…”
Section: Discussionsupporting
confidence: 81%
“…Repeated lithium and ANDRO treatment prevented LDX-induced increases in LPO in rat striatum. Increased generation of reactive oxygen species and free radicals are involved in the pathophysiology of bipolar disorder, as increases in serum/plasma LPO occur in different phases and are associated to illness severity and/or the number of manic episodes (Andreazza et al, 2007;Machado-Vieira et al, 2007;Brown et al, 2014;Sowa--Kućma et al, 2018;Akarsu et al, 2018). In this line, high concentrations of phospholipids make brain tissues more vulnerable to oxidative stress induced by LPO (Banerjee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As specified earlier, a frequent finding in patients with BD is the increase in antioxidant marker levels [116], which is likely part of a compensatory response to prevent oxidative damage. Yumru et al found that serum SOD (an antioxidant marker) was significantly elevated in patients with depression and mania compared with controls [73].…”
Section: Oxidative Damage In Bdmentioning
confidence: 81%